Roost tree characteristics determine use by the white-striped freetail bat (Tadarida australis, Chiroptera: Molossidae) in suburban subtropical Brisbane, Australia - Rhodes, M.; Wardell-Johnson, Grant (Blackwell Publishing Asia, 2006)
We examined factors affecting roost tree selection by the white-striped freetail bat Tadarida australis (Chiroptera: Molossidae), a large insectivorous bat in suburban Brisbane, Australia. We compared biophysical characteristics associated with 34 roost trees and 170 control trees of similar diameter, height and tree senescence characters. Roost trees used by the white-striped freetail bat had significantly higher numbers of hollows in the trunk and branches (P<0.003) and were more likely to contain a large trunk cavity with an internal diameter of >30 cm (P<0.001) than control trees. These trees also accommodated more species of hollow-using fauna (P = 0.005). When comparing roost trees with control trees of similar diameters and heights, roost trees were on average at a later stage of tree senescence (P <0.001). None of the roost trees were found in the large forest reserves fringing the Brisbane metropolitan area despite these areas being used for foraging by the white-striped freetail bat. Although all tree locations in this study were in modified landscapes, roost trees tended to be surrounded by groups of trees and undergrowth. Roost trees provide important habitat requirements for hollow-using fauna in suburban, rural and forested environments.